Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1498460
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of heteronuclear dimers adsorbed on a square lattice

Abstract: Monte Carlo simulation in the grand canonical ensemble has been performed to study phase transitions in monolayer films formed by heteronuclear dimers. The phase diagrams have been estimated for some model systems. The results reveal a great variety of vapor–liquid coexistence behaviors depending on the relative strengths of interactions between molecule segments. The structural transitions have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…If we take a 2D dimer and we add hydrogen bond interaction like in MB water, we can obtain models for alcohols like methanol and t-butanol. Most of the studies to understand the properties of dimers used computer simulations on a lattice [28][29][30][31][32][33][34][35][36] and some also on continuous-space. 27,37,38 This work is an extension of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…If we take a 2D dimer and we add hydrogen bond interaction like in MB water, we can obtain models for alcohols like methanol and t-butanol. Most of the studies to understand the properties of dimers used computer simulations on a lattice [28][29][30][31][32][33][34][35][36] and some also on continuous-space. 27,37,38 This work is an extension of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…N is the number of adsorbed dimers. The term NJ 1 is subtracted in the Hamiltonian since the summation over all the nearest-neighbor site pairs overestimates the total energy by including N bonds belonging to the N adsorbed dimmers [40][41][42]. By the Monte Carlo annealing, we obtained twelve different types of ground states of dimer adsorption on the (6, 0) SWCNT, more than the single-site adsorption.…”
Section: Ground States Of Adsorbates On Swcntsmentioning
confidence: 99%
“…The adsorbed diatomic molecules are modelled as dimers, which occupy two neighboring lattice sites, and we use the dimmer model to describe it [40][41][42]. The Hamiltonian of the System is given as:…”
Section: Ground States Of Adsorbates On Swcntsmentioning
confidence: 99%
“…There are papers devoted to the description of the first order phase transition such as "surface gas -surface liquid" [75,76,80]. The most important conclusion from all these studies is that with increasing molecular size the critical temperature shifts to higher values.…”
Section: The Models Of Dimer and K-mer Adsorptionmentioning
confidence: 99%
“…In the study of phase diagrams of these films interesting phenomena were found. In particular, the coexistence of three phases and a variety of structural transitions, and ordered linear type structure exists even at high temperatures [75].…”
Section: The Models Of Dimer and K-mer Adsorptionmentioning
confidence: 99%